Cyclic loading tests of flexural-failure dominant URM walls strengthened with engineered cementitious composite. (1st September 2019) - Deng, Mingke; Dong, Zhifang; Ma, Ping
Highlights: This paper presents the test results of URM walls strengthened with ECC. URM walls failed with the flexural-dominant mode. ECC layers can significantly improve the ductility of specimens. A calculated mode was proposed for the URM walls strengthened with ECC overlay. Abstract: Engineered cementitious composite (ECC) is a typical fiber reinforced cementitious composite with a strain-hardening behavior in tension and can be easily applied to strength masonry structures. This work studies the static behavior of flexural-failure dominant unreinforced masonry (URM) walls strengthened with ECC overlay. Five URM walls were constructed and four of them were reinforced: a wall strengthened with steel mesh, a wall strengthened with single-side ECC overlay, two walls strengthened with double-sides ECC overlay. One of the two double-sides ECC-strengthened walls was designed with a tie column. The effectiveness of reinforcement plans and tie column on the failure mode, lateral strength, hysteresis response, stiffness degradation, energy dissipation capacity, residual displacement and equivalent viscous damping is analyzed. The experimental results indicate that the ECC retrofit techniques can significantly improve the ductility of URM walls. The walls strengthened with ECC overlay exhibit significant increase in the wall drift and energy dissipation and decrease in the residual displacement. Finally, a calculated model for the ECC reinforced walls was proposed to estimate the maximum lateral strength.